ANALISIS SISTEM OTOMASI KONVEYOR PADA MESIN COOLANT FILTRATION DI PT. MATAHARI MEGAH - Juan Setiawan; Agus Halim; Kevin Raynaldo; Ronald Ogi Pratama (POROS, 2022)
Coolant Filtration Machine is one of the products of PT. Matahari Megah. The purpose of this machine is to recycle residual coolant fluid that has been used in the machining process. Coolant Filtration Machine is working through automation system which involves conveyor system controlled by sensors. The components involved need to be analyzed and calculated properly to work as designed. Hence, calculation for required electricity power to move the wire mesh conveyor used in this machine was done. According to the process, it was concluded that the required power is 60 Watt. A pair of sensors are mounted to control the movement of this conveyor are proximity sensors which monitor the water container and lever limit switch monitoring the paper holder system.